Relationship of Circulating Fetuin-A Levels with Body Size and Metabolic Phenotypes - Hye Soo Chung; Hyun Jung Lee; Soon Young Hwang; Ju-Hee Choi; Hye Jin Yoo; Ji A. Seo; Sin Gon Kim; Nan Hee Kim; Dong Seop Choi; Sei Hyun Baik; Kyung Mook Choi (International Journal of Endocrinology)
Background. Previous studies have suggested the existence of distinct body size subgroups according to metabolic health referred to as metabolically healthy obesity (MHO) and metabolically abnormal but normal weight (MANW) patients. Although nonalcoholic fatty liver disease (NAFLD) is strongly associated with obesity and metabolic syndrome, the relationship between these phenotypes and fetuin-A, a representative hepatokine, has not been explored. Methods. We examined the association between circulating fetuin-A levels, metabolic health phenotypes, cardiometabolic risk parameters, and subclinical atherosclerosis in 290 subjects who were randomly selected from an ongoing cohort study. Results. Fetuin-A concentrations were significantly associated with detrimental anthropometric and laboratory measurements, including increased waist circumference, blood pressure, alanine aminotransferase, fasting plasma glucose, and triglyceride levels. Furthermore, fetuin-A levels were significantly increased in the metabolically abnormal (MA) group compared to the metabolically healthy (MH) group in subjects without obesity (717.1 [632.1, 769.7] vs. 599.5 [502.0, 709.3], P=0.001) and subjects with obesity (704.1 [595.5-880.9] vs. 612.2 [547.9-802.1], P=0.016). In addition, brachial-ankle pulse wave velocity (baPWV), which reflects arterial stiffness, was higher in MA individuals compared to MH individuals. Multiple logistic regression analysis revealed that both individuals without obesity (P for trend = 0.017) and with obesity (P for trend = 0.028) in the higher tertiles of fetuin-A had an increased risk of MA than those in the lowest tertile. Conclusions. This study demonstrates that fetuin-A levels are significantly associated with metabolic health phenotypes, such as MHO and MANW, in Korean adults.